As representações do camponês e do latifundiário brasileiros: trabalhadores rurais e coronéis na cultura política comunista (1922-1964) - Paula Elise Ferreira Soares (2011)
This work aims to recover the imaginary built by militants of the Brazilian Communist Party (PCB) on rural workers and landowners from 1922 to 1964. The PCB was the first Brazilian organization to deal with rural workers and its political culture influenced several left-oriented organizations in the country. Thus, theorists, writers and artists strove to formulate an original program of the party concerning rural workers. The rural was seen as a place of stagnation in the early years of the existence of the party. However, in the 1940s, this idea begins to change and rural workers were seen as revolutionaries, as well as the working class. The rural workers could then have two options: to become progressive if well conducted, or to become exploiter of alien labor, if enriched. Landowners belonged to the latter group. They were seen as lazy fat men and the main enemies of the nation, the country's ties with imperialism. We find the first formulation of an agrarian left-oriented program in Brazil through the journals, theoretical, literary and art works produced by the PCB between 1922 and 1964. We discover also the ideas that marked the comprehension of Brazilian rural workers and landowners for many years to come.